Ireland : Financial Sector Assessment Program-Technical Note on Insurance Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2022)
Ireland's insurance sector is characterized by high penetration and density in both the life and the non-life sector, which, however, stems largely from outward cross-border business (Table 2). In terms of premiums, Ireland hosts the fourth largest insurance sector in the European Union (EU), and assets managed by the insurance industry amount to 117 percent of the GDP, compared to 72 percent for the EU average. The large majority of Irish insurers are subsidiaries of international groups and often have significant interlinkages with related entities within the same group. Extensive intra-group financial links could expose local entities to concentration and other risks. Cross-border business plays an essential role, and Irish insurers hold relevant market shares in other EU member states. Many firms operate on an 'outward' cross-border basis, so that in total less than 30 percent of premiums is written in Ireland.